Optimization of magnetization transfer contrast for EPI FLAIR brain imaging. Issue 5 (5th January 2022) - Demir, Serdest; Clifford, Bryan; Lo, Wei‐Ching; Tabari, Azadeh; Goncalves Filho, Augusto Lio M.; Lang, Min; Cauley, Stephen F.; Setsompop, Kawin; Bilgic, Berkin; Lev, Michael H.; Schaefer, Pamela W.; Rapalino, Otto; et al.
Abstract: Purpose: To evaluate the impact of magnetization transfer (MT) on brain tissue contrast in turbo‐spin‐echo (TSE) and EPI fluid‐attenuated inversion recovery (FLAIR) images, and to optimize an MT‐prepared EPI FLAIR pulse sequence to match the tissue contrast of a clinical reference TSE FLAIR protocol. Methods: Five healthy volunteers underwent 3T brain MRI, including single slice TSE FLAIR, multi‐slice TSE FLAIR, EPI FLAIR without MT‐preparation, and MT‐prepared EPI FLAIR with variations of the MT‐preparation parameters, including number of preparation pulses, pulse amplitude, and resonance offset. Automated co‐registration and gray matter (GM) versus white matter (WM) segmentation was performed using a T1‐MPRAGE acquisition, and the GM versus WM signal intensity ratio (contrast ratio) was calculated for each FLAIR acquisition. Results: Without MT preparation, EPI FLAIR showed poor tissue contrast (contrast ratio = 0.98), as did single slice TSE FLAIR. Multi‐slice TSE FLAIR provided high tissue contrast (contrast ratio = 1.14). MT‐prepared EPI FLAIR closely approximated the contrast of the multi‐slice TSE FLAIR images for two combinations of the MT‐preparation parameters (contrast ratio = 1.14). Optimized MT‐prepared EPI FLAIR provided a 50% reduction in scan time compared to the reference TSE FLAIR acquisition. Conclusion: Optimized MT‐prepared EPI FLAIR provides comparable brain tissue contrast to the multi‐slice TSE FLAIR images used in clinical practice.